STUDI KELAYAKAN BUDIDAYA KELAPA KOPYOR DI KABUPATEN PURBALINGGA - Suliyanto Suliyanto (Faculty of Economics and Business Universitas Jenderal Soedirman, 2009)
The aim of this research is to analyze the visibility kelapa kopyor (ubnornal coconut) business in Purbalingga. The analysis’ tool that used are four aspects they are Market aspect, Tehnique aspect, Sosial economic aspect and Financial Aspect. The market aspect used SWOT analyzes and supply-demand analysis. The Sosial economic aspect used cost-benefit analysis. The Financial aspect used, Payback Period (PP), Net Present Value (NPV), Profitabilitas Indeks (PI), and Internal Rate of Return (IRR). The result of this research shown that investation kelapa kopyor business in Purbalingga was visible.